(untitled) (Global Journal of Human-Social Science, 2012)
The study examines the politics of fuel subsidy removal in Nigeria The descriptive nature of the study has necessitated the extensive use of desk research The paper argues strongly that the policy derives its instrumentality from the theory of development racism which only benefits the rulers of the country and multinational companies and not the citizen This explains the massive protests by the Nigerian Labour Congress Civil Liberty Organisations and the masses of Nigerian that usually accompanied fuel subsidy removal We have recommended that for the smooth operation of the petroleum sub-sector government must always engage the people in policies that will affect them We also recommended for the building of more refineries in order to make the product more available to the people and at an affordable pump price This could be done through private public partnership